Analisis Pengaruh Konten Hiburan Digital Terhadap Pola Hidup Mahasiswa - Anshory Ramadhan; Dwi Artika Urbasari; Nazla Sabirah; Salsabila Rahma; Siti Suaibah Nasution (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The development of digital technology has significantly transformed lifestyles, including those of students at the State Islamic University of North Sumatra (UINSU), particularly through entertainment platforms such as TikTok and Netflix. This study aims to analyze the impact of these platforms on students' lifestyles using a descriptive qualitative approach. Data were collected through interviews and a Google Form questionnaire utilizing a Likert scale, with responses from 30 participants. Findings show that 73.3% of students actively use TikTok daily for 2–5 hours, while 26.7% actively use Netflix, often engaging in binge-watching. Around 70% reported experiencing disrupted sleep patterns due to late-night usage, and 63.3% preferred digital entertainment over face-to-face social interactions. Furthermore, 56.7% admitted to becoming more impulsive in their shopping behavior after exposure to promotional content and influencer-driven lifestyles. Overall, 83.3% of respondents acknowledged direct impacts from using TikTok and/or Netflix, including sleep disturbances, reduced social interaction, or increased consumerist behavior. These findings indicate a shift in students' preferences toward instant, individualistic entertainment, highlighting the influence of digital platforms in reshaping how students manage their time, maintain social relationships, and make everyday consumption decisions.